2018
DOI: 10.24197/aefd.2-3.2018.235-255
|View full text |Cite
|
Sign up to set email alerts
|

Influencia de la viabilidad percibida por los profesores en el desarrollo de estrategias motivacionales sobre la motivación del alumnado en clase Educación Física

Abstract: El objetivo de este trabajo es analizar la percepción de los profesores de educación física respecto a la viabilidad de estrategias para favorecer la satisfacción de las necesidades psicológicas básicas del alumnado (NPB), así como comprobar si dicha percepción influye sobre la satisfacción de las NPB, la motivación auto-determinada, el gusto por la Educación Física (EF) y la importancia concedida a la materia por parte de sus estudiantes. Participaron 66 profesores de EF (M = 42.12; DT = 9.29) y 1577 estudian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
1
3
0
1
Order By: Relevance
“…Regarding the satisfaction of the BPN and autonomous motivation, similar results have been found in previous researches (Moè & Katz, 2020;Moreno-Murcia et al, 2018Pérez-González et al, 2019). For this positive relationship to appear, other authors indicated that it is necessary for the teacher to favor the motivational climate in PE classes through the autonomy support and autonomous motivation to the students (Franco & Coterón, 2018). Students with higher levels of autonomy support from their teacher demonstrate better relationship among peers (Fin et al, 2017;Fin et al, 2019), which are in line with our findings as the autonomous motivation have predicted cooperation and affiliation in the sample.…”
Section: Discussionsupporting
confidence: 84%
“…Regarding the satisfaction of the BPN and autonomous motivation, similar results have been found in previous researches (Moè & Katz, 2020;Moreno-Murcia et al, 2018Pérez-González et al, 2019). For this positive relationship to appear, other authors indicated that it is necessary for the teacher to favor the motivational climate in PE classes through the autonomy support and autonomous motivation to the students (Franco & Coterón, 2018). Students with higher levels of autonomy support from their teacher demonstrate better relationship among peers (Fin et al, 2017;Fin et al, 2019), which are in line with our findings as the autonomous motivation have predicted cooperation and affiliation in the sample.…”
Section: Discussionsupporting
confidence: 84%
“…Despite the proven importance of teachers performing strategies to improve the perception of support for student autonomy, Franco and Coterón [8] found that, for PE professors, strategies oriented at favoring the satisfaction of autonomy were more viable when compared with those oriented to the development of motor competence, to obtain a greater self-determined motivation, satisfaction of the BPN of autonomy and competence, and importance towards PE classes by the students. In this sense, teachers can change their style of teaching and create environments that favor autonomy support [85].…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, this means encouraging the active participation of students during learning activities and recognizing their capabilities [7]. The student's perception of autonomy support (defined as students who perceive the support of their teachers towards their autonomous motivation) helps to highlight students' effort and persistence during PE classes [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maslow propuso que la motivación está en función de las necesidades básicas. (Franco & Coterón., 2018). Estas necesidades son Fisiológicas: La necesidad de tener oxígeno (aire), comida, agua.…”
Section: Teoría De La Instrumentalidadunclassified